Effects of virtual reality motor games on motor skills in children with cerebral palsy: a systematic review and meta-analysis - Xue, Zhuolin; Zhang, Weiqiang; Zhou, Ni; Ma, Pengwei; Yuan, Kun; Zheng, Peiyun; Li, Junfeng; Chang, Jindong (Frontiers in Psychology, 2025)
BackgroundEnhancing motor skills is crucial for the functional development of children with cerebral palsy. Virtual reality has emerged as a promising technology for rehabilitating these children.ObjectiveThe objective of this study was to systematically evaluate the effects of virtual reality motor games on the gross and fine motor skills of children with cerebral palsy.MethodsA comprehensive search was conducted in databases including PubMed, ProQuest, EBSCOhost, Web of Science, and Wanfang Data, covering publications from their inception to June 1, 2024, to identify randomized controlled trials (RCTs) investigating the effects of virtual reality motor games on the gross and fine motor skills of children with cerebral palsy. The quality of the included studies was assessed using the PEDro scale, and data were analyzed with RevMan software (version 5.4).ResultsNineteen studies involving 850 children with cerebral palsy were included. The results indicated that virtual reality motor games significantly improved gross motor skills [mean difference (MD) 1.67, 95% confidence interval (CI): 0.75–2.56; P < 0.001] and fine motor skills [standardized mean difference (SMD) 0.73, 95% CI: 0.30–1.16; P = 0.00008] in children with cerebral palsy.ConclusionsVirtual reality motor games have the potential to significantly enhance both gross and fine motor skills in children with cerebral palsy.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, PROSPERO [CRD42024558713].